2006
DOI: 10.1097/01.prs.0000218715.58016.71
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk of Systemic Fat Mobilization and Fat Embolism as a Consequence of Liposuction: Ex Vivo Study

Abstract: The authors' experiments have demonstrated a significant risk of systemic fat mobilization and fat embolism after liposuction in the animal model. Further clinical investigation is required to evaluate the real clinical risk of this procedure from this perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 20 publications
1
28
1
1
Order By: Relevance
“…It was observed that increasing the number of fat globules is directly related to the time of liposuction 11 . In our study, the liposuction procedure was performed on all animals at time of less than 10 minutes with removal of 8 ml of adipose tissue per animal, contrasting with the 60 minutes cited in other studies 11,12 . The lack of finding may also be attributed to the minimally invasive nature of the technique and choice for reduced surgical time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that increasing the number of fat globules is directly related to the time of liposuction 11 . In our study, the liposuction procedure was performed on all animals at time of less than 10 minutes with removal of 8 ml of adipose tissue per animal, contrasting with the 60 minutes cited in other studies 11,12 . The lack of finding may also be attributed to the minimally invasive nature of the technique and choice for reduced surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies involving liposuction procedures shows techniques more harmful and long duration [11][12][13] . This difference may interfere considerably in the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) However, reports of adverse consequences, among which are fat embolism and FES, are increasingly common. (2)(3)(4)6) Fat embolism is defined as the occurrence of mechanical blockage of the vascular lumen by circulating fat globules. Although it primarily affects the lungs, it can also affect the central nervous system, retina, and skin.…”
Section: Discussionmentioning
confidence: 99%
“…(1) More rarely, there are reports of FES after cosmetic procedures, such as liposuction and fat grafting. (2)(3)(4) In the lungs, fulminant FES manifests as severe respiratory insufficiency and acute respiratory distress syndrome (ARDS), although the emboli can reach the arterial circulation and affect other sites, such as the central nervous system, retina, and skin. (2,3) rial oxygen tension/fraction of inspired oxygen ratio of 32 and a lung injury score of 2.6.…”
Section: Introductionmentioning
confidence: 99%